Sedimentology, Sequence Stratigraphy and Reservoir Characterization of Samana Suk Formation Exposed in Namal Gorge Section, Salt Range, Mianwali, Punjab, Pakistan - Muhammad Hayat; Maqsood ur Rahman2; Noor Ali Khan; Abdullah; Fahad Ali (International Journal of Economic and Environmental Geology, 2016)
Samana Suk Formation of Bathonian-callovain age, exposed in Nammal Gorge Salt Range, has been studied for microfacies and sequence stratigraphic investigation. The formation is mainly composed of limestone, with minor beds of sandstone and marl. The limestone is grey, yellowish and purple in color. Limestone is fine grained, thin to medium bedded and inter-bedded with algal laminations. The sandstone is light yellowish brown, brick red in color, calcareous and quartzose. Within Samana Suk Formation one 2ndorder sequence and two 3rdorder sequences have been identified. Their regional correlation through fine-tuned dating helped to develop basin fill model and to understand facies dynamics. A facie belt comprising a wide belt of carbonate facies characterized by Peloidal Packstone microfacies represents inner ramp setting and Pelletal/ Peloidal Wackstone, Mud-Wackstone and Mudstone microfacies represent the low energy lagoonal environment. The sandstone lithofacies represents high energy beach environment which indicates aggrading to pro-grading pattern. The porosity analysis has been done on different samples of limestone and sandstone. For the porosity analysis the Image J software is used. In limestone the porosity ranges up to 6% while in sandstone the porosity ranging up to 18%. From the field and porosity analysis it is concluded that Samana Suk Formation in study area is good reservoir. Keywords: Salt Range, microfacies, sequence stratigraphy, reservoir characteristics.